An Early Experience of Retrograde Intrarenal Surgery (RIRS) in National Institute of Kidney Diseases and Urology (Bangladesh Journal of Urology, 2020)
Background: Advancements in the endoscopic armamentarium, retrograde intrarenal surgery has become a viable and attractive option for the treatment of renal stones because of its high stone-free rates (SFRs) and low morbidity.Objective: To describe our experience and outcome of RIRS for the treatment of renal stones and to assess its effectiveness and safety.Design, setting, and participants: A retrospective analysis of 60 patients who underwent RIRS for renal stones at our institute between January 2018 to December 2018 was performed.Surgical procedure: Flexible ureteroscopy and laser lithotripsy using a standardized technique with last-generation flexible ureteroscopes (Flex-Xc) using Holmium-YAG laser.Outcome measurements and statistical analysis: Clinical data were collected and intraoperative and postoperative outcomes were assessed (Ureteral access sheath placement, operation time, hospital stay, stone free rate, post-operative blood transfusion & fever, need for second session of RIRS. A descriptive statistical analysis was performed.Results and limitations: The mean overall stone size was 13±3 mm. Pre stenting done in all cases. Ureteral access sheath placement was possible in 54(90%) patients. At 1 month follow-up, the overall primary SFR was 86.67%(52 cases), the secondary SFR was 96.67%(58 cases).The mean operative time was 91.96±18.7 min. Mean hospital stay was 1.86±1.02 days. Complications were reported in 8 (13.33%) patients overall, with fever in 6 patients (10%), steinstrasse in 2(3.33%) patients need for second session RIRS in 6 patients (10%).No patient needed blood transfusion. The main limitation of the study is the retrospective nature.Conclusions: RIRS performed using a flexible ureterorenoscope marked the beginning of a new era in urology. It is safe and effective procedure and an alternative to extracorporeal shock wave lithotripsy (ESWL) and Percutaneous nephrolithotomy (PCNL) in the treatment of selected renal stones.Bangladesh Journal of Urology, Vol. 23, No. 1, January 2020 p.3-10